2021
DOI: 10.1177/02698811211032609
|View full text |Cite
|
Sign up to set email alerts
|

Association study of BDNF Val66Met gene polymorphism with bipolar disorder and lithium treatment response in Indian population

Abstract: Background: The association of the Val66Met (rs6265) polymorphism in the brain-derived neurotrophic factor ( BDNF) gene with bipolar disorder (BD) and response to lithium treatment has been suggested, though inconsistently. The considerable diversity of allele frequency across different populations contributes to this. There is no data from South Asia till date. Hence, we examined the association of this polymorphism in BD cases from India, and its association with lithium treatment response. Methods: BD patie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 73 publications
(67 reference statements)
0
8
0
3
Order By: Relevance
“…A study by Paul et al (2021) revealed significant differences in the rs6265 polymorphism, notably observing a higher occurrence of the G (Val) allele among BD patients from India [ 116 ]. Additionally, in a recent study by Yoldi-Negrete et al (2022), it was concluded that being an rs6265 Met carrier is a significant predictor of impaired functioning in individuals with BD-I [ 117 ].…”
Section: Polymorphismmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Paul et al (2021) revealed significant differences in the rs6265 polymorphism, notably observing a higher occurrence of the G (Val) allele among BD patients from India [ 116 ]. Additionally, in a recent study by Yoldi-Negrete et al (2022), it was concluded that being an rs6265 Met carrier is a significant predictor of impaired functioning in individuals with BD-I [ 117 ].…”
Section: Polymorphismmentioning
confidence: 99%
“…However, in their meta-analysis, Ehret et al (2013) concluded that the Val66Met polymorphism cannot predict lithium treatment response in BD patients [ 143 ]. Similarly, Paul et al (2021) did not find a significant association between the rs6265 polymorphism and the response to lithium treatment in BD patients from India [ 116 ]. Interestingly, Lee et al (2014) found a significant association between the addition of memantine to valproic acid in Val66Met heterozygote carriers treated for BD-II, resulting in a decrease in depressive symptoms compared to the use of valproic acid with a placebo [ 144 ].…”
Section: Polymorphismmentioning
confidence: 99%
“…Other studies have linked BDNF rs1519480 with BD (Liu et al, 2008), particularly the allele C of this SNP reported an association with type I bipolar disorder (Sears et al, 2011). BDNF has also been involved in treatment response to antidepressants (Cardoner et al, 2013) and mood stabilizers (Paul et al, 2021), which might be explained by the effects of this neurotrophic agent on brain structure (Post, 2007). BDNF rs7124442 was associated in previous research with treatment response to antidepressants (Domschke et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Faßbender et al (2021) report a study which examined GABAergic modulation of performance in response inhibition and interference control tasks and found evidence for GABAergic involvement in performance on both types of tasks. Paul et al (2021) examined the association of the BDNF Val66Met gene polymorphism with bipolar disorder and lithium treatment response in an Indian population. Biomarkers of lithium response would be a great clinical utility; however, the authors report that although the Val(G) allele of BDNF Val66Met polymorphism is associated with risk of BD in their sample, this was not related to response to lithium.…”
mentioning
confidence: 99%